Living with Diabetes: Keeping Track of Your Blood Glucose - Linda B. Bobroff (EDIS, 2010)
FCS8893, a 3-page illustrated fact sheet by Linda B. Bobroff, describes how patient self-monitoring and hemoglobin A1C testing are used to help persons with diabetes attain their treatment goals. Published by the UF Department of Family Youth and Community Sciences, January 2010.